THERAPEUTIC EFFECTS OF WEST INDIAN ELM LEAF EXTRACT (GUAZUMA ULMIFOLIA) IN OBESE WISTAR RATS: INHIBITING INFLAMMATION, NECROSIS AND PANCREATIC CELL DEGENERATION - Balqis Salsabila (2023)
ABSTRACT Obesity is a chronic disease with increased accumulation of body fat. Obesity can trigger changes in the body's metabolism that play a role in the occurrence of insulin resistance. This can cause damage to pancreatic cells. Orlistat as an anti-obesity drug has the ability to inhibit fat absorption in the intestine. Tannins, saponins, alkaloids, and flavonoids are secondary metabolites contained in the west indian elm leaves (Guazuma ulmifolia) which can be used as a slimming agent, diabetes, tonic, astringent. This type of research used experimental research which described histopathological parameters to see the scale of the progression of pancreatic cell necrosis, as many as 30 Wistar rats were induced by high-fat feed and divided into 6 sample groups consisting of 3 control groups and 3 treatment groups which were given west indian elm leaves extract with doses of 0.2, 0.4 and 0.8 gr/KgBW. The rats underwent necropsy and then the pancreatic tissue was taken and stained with Hematoxylin Eosin. Kruskal-Wallis test and Mann Whitney Post-Hoc, significant results were obtained (P Value <0.05) between the negative control group and treatment group 1 (0.2 gr/KgBW), and treatment 2 (0.4 g/KgBW). The conclusion from this study is that West Indian Elm Leaves have the potential to inhibit inflammation, pancreatic cell necrosis and have a therapeutic effect equivalent to orlistat and 0.4 g/KgBW against cell degeneration has the same therapeutic effect as orlistat but not adequate. Keyword: Cell degeneration, Histopathology, Inflammation, Necrosis, Orlistat, West Indian Elm Leaves.